Morphology and Mechanical Property of Electrospun PA 6/66 Copolymer Filament Constructed of Nanofibers (Journal of Fiber Bioengineering and Informatics, 2018)
A technique for spinning continuous filaments constructed of nano-scale fibers instead ofnon-woven obtained by general electrospinning was described in the paper. Polyamide 6/66 copolymersolution in 88% formic acid was used as the spinning material. The relationships between the fibermicrostructures, filament mechanical properties and spinning parameters: spinneret tip to collectorvertical distance (TD), rotation speed (RS) were investigated. Post-drawing was performed to theas-electrospun continuous filament. The research results revealed that increase of TD and RS couldimprove the fiber's uniaxial alignment and crystal structure, consequently the strength of the filamentwas enhanced. After being post-drawn, the stress and strain at break of the electrospun polyamide 6/66copolymer filament was well improved.